2022
DOI: 10.1177/00343552221127032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Optimism, Hope, Resilience, Coping Flexibility, Secure Attachment, and PERMA as a Well-Being Model for College Life Adjustment of Student Veterans: A Hierarchical Regression Analysis

Abstract: The purpose of this study is to examine (a) to what extent demographic covariates, foundational and emerging positive psychology traits (FEPPTs), and PERMA uniquely predict college life adjustment, health-related quality of life (HRQOL), and life satisfaction of student military veterans; (b) PERMA as a happiness and well-being model for college life adjustment, HRQOL, and life satisfaction among student veterans; and (c) FEPPTs as predictors of PERMA. In addition, we tested whether total PERMA scores mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 98 publications
0
20
0
Order By: Relevance
“…Positive psychology, defined as the scientific study of positive human traits and experiences, has been integrated into rehabilitation practice and research (e.g., Duckworth, Steen, & Seligman, 2005; Martz & Livneh, 2016; Moran & Nemec, 2013; Sheldon & King, 2001). Positive psychology researchers have emphasized that the focus of psychology and rehabilitation should not be only on psychopathology, functional limitations, and weaknesses but also on happiness, functioning, strengths, and well-being (Duckworth et al, 2005; Martz & Livneh, 2016; Tansey et al, 2018; Umucu, 2017). The rehabilitation literature has also revealed that positive psychology constructs (e.g., hope, resilience, meaning in life, flourishing) are linked to positive health and rehabilitation outcomes such as well-being and psychosocial adaptation to disability (Martz & Livneh, 2016; Moser et al, 2020; Umucu, Grenawalt, et al, 2019).…”
mentioning
confidence: 99%
“…Positive psychology, defined as the scientific study of positive human traits and experiences, has been integrated into rehabilitation practice and research (e.g., Duckworth, Steen, & Seligman, 2005; Martz & Livneh, 2016; Moran & Nemec, 2013; Sheldon & King, 2001). Positive psychology researchers have emphasized that the focus of psychology and rehabilitation should not be only on psychopathology, functional limitations, and weaknesses but also on happiness, functioning, strengths, and well-being (Duckworth et al, 2005; Martz & Livneh, 2016; Tansey et al, 2018; Umucu, 2017). The rehabilitation literature has also revealed that positive psychology constructs (e.g., hope, resilience, meaning in life, flourishing) are linked to positive health and rehabilitation outcomes such as well-being and psychosocial adaptation to disability (Martz & Livneh, 2016; Moser et al, 2020; Umucu, Grenawalt, et al, 2019).…”
mentioning
confidence: 99%
“…Previous research has demonstrated that student veterans commonly experience mental health concerns (e.g., posttraumatic stress disorder [PTSD]; Barry et al, 2014; Umucu et al, 2018, in press; Umucu, Lee, et al, 2022; Umucu, Rumrill, et al, 2022), physical and sensory disabilities (Bilmes, 2007; Church, 2009), and traumatic brain injuries (TBIs; RAND Corporation, 2008) that negatively influence their experiences in higher education (Barry et al, 2014; Umucu, 2017). In a systematic review, Barry et al (2014) found binge drinking was positively related to PTSD and psychosomatic symptoms for student veterans, but not for nonveteran students.…”
Section: Student Veterans’ Needs In Higher Educationmentioning
confidence: 99%
“…Specifically for veterans, resilience was reported to be associated with decreased PTSD, suicidality and depressive symptoms, and reduced alcohol problems (Green et al, 2010; Pietrzak et al, 2010; Zang et al, 2017). Given that resilience enables one to respond to stressful events in an adaptive way and is associated with positive mental health outcomes, investigating student veterans’ resilience and the mechanisms by which it can be enhanced or reduced is crucial (Umucu, 2017).…”
Section: Student Veterans’ Needs In Higher Educationmentioning
confidence: 99%
“…Higher education is a critical public health tool to achieve economic success, upward mobility, and improved quality of life ( 1 3 ). This stance aligns well with research documenting that education increases average lifetime earnings, societal contributions, healthier lifestyle, and reduces poverty, tendency to commit crimes, and unemployment ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar research ( 8 ) reported that emotional strengths were positively associated with GPA in SVDs. Finally, Umucu ( 39 ) examined positive psychology model as a college adjustment and wellbeing model for SVD and found that positive psychology is a promising approach for SVDs given it focuses on strengths.…”
Section: Introductionmentioning
confidence: 99%